Readings in planning theory - Fainstein, Susan S.; Fainstein, Susan S.; Campbell, Scott, 1958- (Chichester, West Sussex ; Malden, MA : Wiley-Blackwell, 2012)
"The third edition of the highly successful Readings in Planning Theory continues its well established role in defining the most current debates within the field of planning theory - identifying its boundaries, presenting the works that constitute its central focus, and addressing the central issues that face planners as theorists and practitioners. While maintaining an emphasis on developing an understanding of the process and substance of planning within real world constraints, readings in the new edition reflect many of the developments and rapidly changing dynamics of today's globalized world. Editorial updates and the addition of some 13 new readings place an emphasis on emergent themes in planning theory, including changing approaches to modernism, urbanism, communicative action, power, inequality, and justice in the city. A major new section is devoted to planning in a globalized world, with readings addressing the impact of theories of globalization and of theories of development on planning theory. Essays continue to address the role of planning in developing the 'good' city and region within the constraints of a capitalist political economy and a democratic political system, while seeking explanations and guides to planning practice based on analyses of the political economies of the U.S., U.K., and other nations. Building on its established success and well earned reputation, the third edition of Readings in Planning Theory is the definitive work in this increasingly important field"--
Machine generated contents note: Introduction: The Structure and Debates of Planning Theory.I. Foundations of 20th Century Planning Theory.Section Introduction.1. Robert Fishman, Urban Utopias: Ebenezer Howard, Frank Lloyd Wright and Le Corbusier.2. Jane Jacobs, The Death and Life of Great American Cities.3. John Friedmann, The Good City: In Defense of Utopian Thinking.II. Planning: Justifications and Critiques.Section Introduction.4. Heather Campbell and Robert Marshall, Utilitarianism's Bad Breath? A Re-evalution of the Public Interest Justification for Planning.5. Richard E. Foglesong, Planning the Capitalist City.6. Leonie Sandercock, Mongrel Cities.7. James C. Scott, Seeing Like a State: How Certain Schemes to Improve the Human Condition Have Failed.8. Tim Love, Urban design after Battery Park City.III. Planning Types/Normative frameworks.Section Introduction.9. Susan S. Fainstein, Planning Theory and the City.10. Charles E. Lindblom, The Science of Muddling Through.11. Paul Davidoff, Advocacy and Pluralism in Planning.12. John Forester, Challenges of Deliberation and Participation.13. Patsy Healey, Traditions of Planning Thought.IV. Planning in Action: Successes, Failures, and Strategies.Section Introduction.14. Matti Siemiatycki, Implications of Private-Public Partnerships on the Development of Urban Public Transit Infrastructure: The Case of Vancouver, Canada.15. James deFilippis, Collective Ownership and Community Control and Development: The Long View.16. Vivien Lowndes, Citizenship and Urban Politics.17. Bent Flyvbjerg, Bringing Power to Planning Research: One Researcher's Praxis Story.V. Race, Gender and City Planning.Section Introduction.18. Iris Marion Young, Inclusion and Democracy.19. June Manning Thomas, The Minority-race Planner in the Quest for a Just City.20. Dolores Hayden, Nurturing: Home, Mom and Apple Pie.21. Michael Frisch, Planning as a Heterosexist Project.VI. Conflicting Priorities.Section Introduction.22. Scott Campbell, Green Cities, Growing Cities, Just Cities? Urban Planning and the Contradictions of Sustainable Development.23. American Institute of Certified Planners, Code of Ethics and Professional Conduct.24. Frank Fischer, Public Policy as Discursive Construct: Social Meaning and Multiple Realities.25. Nicholas Low and Brendan Gleeson, Environmental Justice.26. Margaret Kohn, The Mauling of Public Space.VII Planning in a Globalized World.Section Introduction.27. Ward Steven, Reexamining the International Diffusion of Planning.28. Peter Evans, Political Strategies for More Livable Cities.29. Yang Zheng and Ke Fang, Is history repeating itself? Urban Renewal in the United States to Inner-City Redevelopment in China.30. Oren Yiftachel, Re-engaging Planning Theory? Towards 'South-Eastern' Perspectives.
Includes bibliographical references and index.
Keywords: City planning; ARCHITECTURE / Urban & Land Use Planning